Strongyloidiasis and Diffuse Alveolar Hemorrhage in a Patient with Systemic Lupus Erythematosus - Fernando Gonzalez-Ibarra; Parag Chevli; Lindsey Schachter; Maninder Kaur; Sahar Eivaz-Mohammadi; Basheer Tashtoush; Jioty Matta; Amer K. Syed; Valentin Marian (Case Reports in Medicine)
The presence of Strongyloides stercoralis infection in patients with systemic lupus erythematosus (SLE) has been described previously. Strongyloides stercoralis hyperinfection syndrome (SHS) that usually develops in patients under immunosuppressive therapy may affect a variety of organs, but the presentation with diffuse alveolar hemorrhage (DAH) is rare with only a few cases described in the literature. We present the case of a 36-year-old Hispanic female with a past medical history relevant for SLE and a recent diagnosis of lupus nephritis and hypertension. The patient who developed sudden and progressive abdominal pain and respiratory distress, with the presence of bilateral crackles and severe hypoxemia, is currently under treatment with steroids and cyclophosphamide for worsening of lupus nephritis. The patient underwent endotracheal intubation and mechanical ventilation, and computed tomography showed the presence of bilateral pulmonary infiltrates suggestive of DAH. Bronchoalveolar lavage was done and showed the presence of filariform larvae, morphologically consistent with Strongyloides stercoralis. Treatment with ivermectin was started and patient responded to treatment with improvement of clinical status. In conclusion, the development of SHS in patients with lupus, especially when receiving immunosuppressive therapy, is a severe and potentially fatal complication. Early detection and treatment may decrease mortality.